Individual changes in zooplankton pigmentation in relation to ultraviolet radiation and predator cues. (17th May 2016) - Brüsin, Martin; Svensson, P. Andreas; Hylander, Samuel
Abstract: Copepods are common crustaceans in aquatic systems and one of the most important producers of carotenoid astaxanthin pigments, which can enhance the animals' resistance against potentially damaging ultraviolet radiation (UVR), but at the same time, increases the risk of fish predation. Previous studies have demonstrated that copepods have different pigmentation levels matching the current threat level in terms of UVR and fish occurrence. However, these other studies have quantified population‐levels changes in pigmentation, making it difficult to disentangle the role of individual phenotypic colour changes from that of selection. We quantified carotenoid‐based pigmentation with colorimetric methods, which enabled us to track changes within individual copepods. Two species of copepods, Diaptomus castor and Eudiaptomus gracilis, were exposed to high and low UVR and fish cues in a factorial design. L*a*b* colour values (CIE; Commission International de l'Eclairage) were extracted from digital photographs of each copepod and used as proxies for carotenoid concentration. Our results showed that individual copepods significantly changed their pigmentation in response to both UVR and fish cues within a period of 2 weeks. However, the responses differed between sexes and between adults and juveniles. UVR effects were present in all life‐stages whereas fish effects were only detected in juveniles, with largest responses in D. castor . This confirms that carotenoid pigmentation is a phenotypically plastic trait, and highlights that strategies for trading off risks of UVR and predation differ between males and females as well as between life‐stages.